SOSIALISASI DAN PELATIHAN PEMANFAATAN BIOGAS DARI KOTORAN TERNAK DAN JERAMI PADI SEBAGAI SUMBER ENERGI ALTERNATIF RAMAH LINGKUNGAN - Fadli Irsyad; Delvi Yanti; Andasuryani Andasuryani (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2018)
This activity aims to transfer knowledge and technology in the use of livestock manure and rice straw as an environmentally friendly alternative energy source, namely biogas, so that farmers get social and economic benefits from their own waste. The methods used in the implementation of this activity are lectures, demonstrations, and experiments. The results of the socialization and training activities on the use of biogas from livestock manure and rice straw can achieve the objectives in accordance with the objectives of community service activities, this can be seen from the increase in participants' understanding of the processing of waste into biogas after 50% of activities.